2021
DOI: 10.18097/pbmc20216705443
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in metabolism of amino acids — precursors of gasotransmitters — in the premature birth

Abstract: The content of amino acids — sources of gasotransmitters and the activity of enzymes of their metabolism have been studied in the placenta and amniotic fluid in full-term and complicated by preterm birth (PB). Determination of amino acids was carried out using an automatic analyzer; specific spectrophotometric methods were used to assess the activity of enzymes. The development of PB is accompanied by changes in the amino acid level already in the second trimester of pregnancy. Correlation of differently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a reduction in H 2 S causes oxidative stress. H 2 S is a gasotransmitter; gasotransmitters are defined as small, endogenous molecules that play an active role in regulating intracellular and intercellular signaling systems and in neuromodulation 67,131,132 . H 2 S behaves as an antioxidant and potentially possesses influence in regulating oxidative stress in chronic hypoxia caused PH 133 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a reduction in H 2 S causes oxidative stress. H 2 S is a gasotransmitter; gasotransmitters are defined as small, endogenous molecules that play an active role in regulating intracellular and intercellular signaling systems and in neuromodulation 67,131,132 . H 2 S behaves as an antioxidant and potentially possesses influence in regulating oxidative stress in chronic hypoxia caused PH 133 .…”
Section: Resultsmentioning
confidence: 99%
“…PE is considered as a sign of cellular apoptosis [ 36 ], while PC is a constitutive plasma membrane lipid and the major transport form of DHA in plasma [ 37 ]. The imbalance of amino acids in the fetoplacental system in PTB is accompanied by a change in the production of their low molecular weight derivatives gas transmitters (NO, CO) [ 38 ]. Previous studies have reported on amino acids and acylcarnitines being potential markers of gestational age [ 39 ].…”
Section: Discussionmentioning
confidence: 99%